2002
DOI: 10.1002/pse.98
|View full text |Cite
|
Sign up to set email alerts
|

Transferability of fracture mechanics parameters to fracture performance evaluation of welds with mismatching

Abstract: In order to evaluate fracture performance of steel welded structures, the fracture mechanics approach has been adopted. However, it has frequently been pointed out that conventional fracture mechanics parameters are not necessarily applicable to all cases. This inconsistency is due to the difference of stress-strain behaviour depending on plastic constraints in the vicinity of a crack tip between the fracture toughness testing specimen and the practical structures. Accordingly, the transferability of the fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…When the crack is located in the higher strength material the crack resistance is shifted to lower values. In the case of undermatching this is quite opposite [20]. …”
Section: Welding Residual Stressesmentioning
confidence: 93%
See 1 more Smart Citation
“…When the crack is located in the higher strength material the crack resistance is shifted to lower values. In the case of undermatching this is quite opposite [20]. …”
Section: Welding Residual Stressesmentioning
confidence: 93%
“…Fig. 17 Effect of strength mismatch in the vicinity of the notch tip on the distribution of fracture toughness in terms of the critical CTOD, a crack in the higher strength material; b crack in the lower strength material; according to [20] Figure 18c illustrates an assessment for unstable failure. Whereas (a) and (b) are based on a single toughness value, K mat , (c) uses an R curve such as shown in (Fig.…”
Section: Generalmentioning
confidence: 99%
“…A pressure vessel is a component of Stirling engine as container designed to hold gases or liquids at a pressure substantially different from the ambient pressure. Pressure vessels can be dangerous, and fatal accidents have occurred in the history of their development and operation, thus in present research determination of quality assessment of high strength steel used for pressure vessel design is necessary [1][2][3][4]. Pressure vessel of prototype Stirling engine operated under 210 O C as a hot cylinder and it is made by high temperature resistance steel 10CrMo10V5 and welded together with two undermached welds ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In the assessment of pressure vessels as a welded structures the consideration of both strength mismatching and transferability cannot be avoided. In this paper we first review the effects of the mismatch observed in pressure vessel with two welded joints on strength and fracture, and show that the plastic constraint due to strength mismatching plays an important role in fractureinitiation behavior for ductile and brittle cracks which appeared in the pressure vessels [3]. Finally, for all testing of pressure vessel and the steel specimens the standard test procedures were used for determining the weldability and quality assessment of high strength steel.…”
Section: Introductionmentioning
confidence: 99%
“…Another problem in toughness evaluation of welds is the very local response of weld imperfections. Quintana et al [7], Satho et al [8] and Toyoda et al [9] focus on local brittle zones which can affect crack initiation and growth in a drastic way. Cleavage can be initiated in an otherwise ductile material.…”
Section: Introductionmentioning
confidence: 99%